1991
DOI: 10.1152/ajpregu.1991.261.4.r782
|View full text |Cite
|
Sign up to set email alerts
|

BAY K 8644 and nifedipine alter halothane but not caffeine contractures of malignant hyperthermic muscle fibers

Abstract: The purpose of these experiments was to determine if the Ca2+ agonist BAY K 8644 and the Ca2+ antagonist nifedipine alter the mechanical responses of malignant hyperthermia-susceptible (MHS) skeletal muscle to halothane and caffeine. Muscle fiber bundles were dissected from MHS porcine skeletal muscle and exposed to BAY K 8644 (10 microM), nifedipine (1 microM), low-Ca2+ media [Ca2+ replaced by 1 mM ethylene glycol-bis(beta-aminoethyl ether)-N,N,N',N'-tetraacetic acid], or diltiazem (30 microM) administered al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…This observation suggests that one of the retrograde effects of R163C mutation on the L-type channel activity of the DHPR is to facilitate entry of the channel into the long–open gating state (i.e., mode 2; Nowycky et al, 1985), which might explain the enhanced potentiation by ±Bay K 8644. Interestingly, Bay K 8644 enhances pharmacologically (halothane or isofluorane) induced contractures in both swine and human MHS muscle (Williams et al, 1991; Adnet et al, 1992), consistent with the idea that altered L-type current may contribute to the pathogenesis of this disease.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This observation suggests that one of the retrograde effects of R163C mutation on the L-type channel activity of the DHPR is to facilitate entry of the channel into the long–open gating state (i.e., mode 2; Nowycky et al, 1985), which might explain the enhanced potentiation by ±Bay K 8644. Interestingly, Bay K 8644 enhances pharmacologically (halothane or isofluorane) induced contractures in both swine and human MHS muscle (Williams et al, 1991; Adnet et al, 1992), consistent with the idea that altered L-type current may contribute to the pathogenesis of this disease.…”
Section: Discussionsupporting
confidence: 77%
“…Williams et al (1991) showed that Bay K 8644 lowers the threshold for halothane-induced contractures in MHS swine muscle fibers. Because the DHPR is the molecular target for Bay K 8644, we tested directly how this agonist affected L-type currents in R163C Het and Hom myotubes.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative and nitrosative modifications of RyR1 and other muscle proteins result in a feed-forward cycle that drives both the myopathy and the EHR [17]. Several groups have suggested that Ca 2+ influx may contribute to sustained Ca 2+ increases associated with the MH response [43][44][45][46], but the possibilities that Ca 2+ influx via stretch-, store-, or voltage-operated Ca 2+ channels contributes to the EHR in the YS mice remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%